Even silence has an end : my six years of captivity in the Colombian jungle - Betancourt, Ingrid (New York : Penguin Press, 2010)
Ingrid Betancourt tells the story of her captivity in the Colombian jungle, sharing teachings of resilience, resistance, and faith. Born in Bogotá, raised in France, Betancourt at age 32 gave up a life of comfort and safety to return to Colombia to become a political leader in a country that was being slowly destroyed by terrorism, violence, fear, and hopelessness. In 2002, while a candidate in the Colombian presidential elections, she was abducted by the FARC. She spent the next six and a half years in the depths of the jungle as their prisoner. Chained day and night for much of her captivity, she succeeded in getting away several times, always to be recaptured. The facts of her story are astounding, but it is Betancourt's indomitable spirit that drives this very special account, bringing life, nuance, and profundity to the narrative.
Keywords: Betancourt, Ingrid, -- 1961- -- Captivity, 2002-2008; Hostages -- Colombia -- Biography; Political kidnapping -- Colombia